Komparasi Implementasi Kurikulum 2013 dan Kurikulum Merdeka di Madrasah Aliyah Negeri 19 Jakarta - Khayrani Amelia; Muhammad Arifin Rahmanto (CV. Creative Tugu Pena, 2024)
This research was conducted with the aim of finding comparisons regarding the implementation of the 2013 curriculum and the independent curriculum at Madrasah Aliyah Negeri 19 Jakarta. The research method used was descriptive qualitative, data collection was carried out by observation, interviews, documentation and data analysis. The results of the research show differences between the 2013 curriculum and the independent curriculum, namely in the implementation of the 2013 curriculum using Learning Implementation Plans (RPP), Syllabus, Content Competencies (KI), Basic Competencies (KD, Minimum Completeness Criteria (KKM). Meanwhile in the independent curriculum, Teaching Modules, Flow of Learning Objectives (ATP), Learning Achievements (CP), Learning Objectives (TP), Criteria for Achieving Learning Objectives (KKTP). Obstacles were also found during the implementation of the 2013 curriculum and the independent curriculum, such as a lack of counseling regarding the procedures for implementing the curriculum so that schools could implement it. adapting from the transition from the 2013 Curriculum to the Independent Curriculum and the role of teachers in participating in Independent Curriculum training.